Moral Development on Inmates as the Efforts to Prevent Recidivists - Juddin, Nurhayati; Kusdarini, Eny; Hamimu, Usman (Humaniora: Journal of Indonesia Culture and Society, 2021)
The research aimed to comprehend the guidance given to inmates to build their mental, good morals, and to be able to absorb positive values of life demands based on the values, norms, and morals implemented in society to prevent recidivists. The problem formulation was how the forms of development of inmates in the Kendari Class IIA Prison of Correctional Institution prevent recidivists. The research was conducted at Kendari Class IIA Prison of Correctional Institution. Descriptive research and a qualitative approach were implement. There were three informants and respondents: the Head of the Kendari Class IIA Prison, the Head of Class IIA Kendari Prison Development, and the Head of Community Guidance and Care of Class IIA Prisons in Kendari, and 30 inmates as respondents and recidivists. The data were collected by conducting library research and field research that consisted of observations, interviews, questionnaires, and documentation. The results reveal that the forms of guidance for inmates in Kendari Class IIA of correctional officers to prevent recidivists are religious awareness building, intellectual capacity building, legal awareness building, and integration with the community (social). Applying a guidance pattern for the inmates is expected to be a part of the tools for correctional officers, especially for those who work in correctional institutions.